Storytelling of Destinations Through Travel Writing - Satrya, I Dewa Gde (iora, 2023)
Traveling is a pleasant experience. For marketers, the media to promote tourist destinations requires honest recognition from tourists who have visited. Currently, a tourism promotion tool can be carried out using a place storytelling approach that is packaged into a travel writing book. This article is the result of qualitative research using the primary data source of interviewing travel writers and studying travel writing works. Secondary data comes from literature studies. The formulation of the problem in this research is how to implement place storytelling through travel writing? The conclusion of this study is that originality is the main key to place storytelling and travel writing books are an effective promotional tool for marketing tourist destinations.